Methanol extract from kesambi (Schleichera oleosa (L.) oken) stem bark as a natural antioxidant to increase crude palm oil (CPO) quality - Weny J A Musa; Nurhayati Bialangi; Diky Kurniawan; M Amrin Sunardi; Ninik Triayu susparini; Sriwijayanti Sriwijayanti; Boima Situmeang (Pascasarjana Universitas Negeri Medan, 2021)
The content of active compounds in methanol extract of kesambi stem bark (Scheleicera oleosa) is known to have good antioxidant activity. Methanol extract of kesambi stem bark contain flavonoid and fenolic compounds. The purpose of this study was to evaluate the methanol extract of kesambi in inhibiting the oxidation of crude palm oil (CPO). In this study, the extraction of kesambi stem bark was carried out with methanol solvent. Antioxidant activity test of methanol extract of kesambi using the DPPH method. The parameters observed were free fatty acids (FFA) values, acids value, and DOBI (Deterioration of Bleachability Index). The used concentration of natural antioxidant were 200; 400; 600; 800 and 1000 ppm. Based on the results of this study, the natural antioxidant of methanol extract of Kesambi stem bark (Schleichera oleosa) can reduce levels of free fatty acid numbers, acid value, and DOBI value. Actioxidant activity methanol extract of kesambi stem bark shown IC50 42.092 ppm. The lowest FFA levels and acid numbers were obtained from samples with addition of 1000 ppm natural antioxidants with free fatty acid (4.1%), acid value (7.7 mg KOH/g) while the DOBI value increased to 1.331. Furthermore, FFA value meets the CPO quality standard, according to SNI-01-2901-2006. Keywords: Crude palm oil, antioxidant, free fatty acid (FFA), acid value